Abnormal Static and Dynamic Local-Neural Activity in COPD and Its Relationship With Pulmonary Function and Cognitive Impairments - Lv, Zhi; Chen, Qingqing; Jiang, Yinling; Hu, Panpan; Zhang, Lei; Bai, Tongjian; Wang, Kai; Wang, Yongsheng; Fan, Xiaoyun (Frontiers in Human Neuroscience, 2021)
Patients with chronic obstructive pulmonary disease (COPD) are characterized by attenuated pulmonary function and frequently reported with cognitive impairments, especially memory impairments. The mechanism underlying the memory impairments still remains unclear. We applied resting-state functional magnetic resonance imaging (RS-fMRI) to compare the brain local activities with static and dynamic amplitude of low-frequency fluctuations (sALFF, dALFF) among patients with COPD (n=32) and healthy controls (HC, n=30). Compared with HC, COPD patients exhibited decreased sALFF in the right basal ganglia and increased dALFF in the bilateral parahippocampal/hippocampal gyrus. The reduced the left basal ganglia were lower oxygen partial pressure. Besides, the increased dALFF in the left hippocampal/parahippocampal cortex was associated poor semantic-memory performance and the increased dALFF in the left hippocampal/parahippocampal cortex was associated the forced vital capacity. The present study revealed the abnormal static and dynamic local-neural activities in the basal ganglia and parahippocampal/hippocampal cortex in COPD patient and its relationship with poor lung function and semantic-memory impairments.